Evaluation of two polyethylene bags in preventing admission hypothermia in preterm infants: a quasi-randomized clinical trial - Ana L.C. Possidente; Ivan G.M. Bazan; Helymar C. Machado; Sergio T.M. Marba; Jamil P.S. Caldas (Elsevier, 2023)
Objective: To compare two polyethylene bags in preventing admission hypothermia in preterm infants born at <34 weeks gestation. Method: Quasi-randomized unblinded clinical trial conducted at a level III neonatal unit between June 2018 to September 2019. The authors assign infants between 240/7 and 336/7 weeks' gestation to receive NeoHelp™ bag (intervention group) or a usual plastic bag (control group). The primary outcome was admission hypothermia, considering an axillary temperature at admission to the neonatal unit of <36.0 °C. Hyperthermia was considered if the admission temperature reached 37.5 °C or more. Results: The authors evaluated 171 preterm infants (76, intervention group; 95, control group). The rate of admission hypothermia was significantly lower in the intervention group (2.6% vs. 14.7%, p = 0.007), with an 86% reduction in the admission hypothermia rate (OR, 0.14; 95% CI, 0.03-0.64), particularly for infants weighing >1000 g and >28 weeks gestation. The intervention group also had a higher median of temperature at admission - 36.8 °C (interquartile range 36.5-37.1) vs. 36.5 °C (interquartile range 36.1-36.9 °C), p = 0.001, and showed a higher hyperthermia rate (9.2% vs. 1.0%, p = 0.023). Birth weight was also associated to the outcome, and it represented a 30% chance reduction for every 100-g increase (OR, 0.997; 95% CI, 0.996-0.999). The in-hospital mortality rate was similar between groups. Conclusion: The intervention polyethylene bag was more effective in preventing admission hypothermia. Nonetheless, the risk of hyperthermia is a concern during its use.